Seminar and Education on The Evaluation of Antibiotic Use in Acute Respiratory Infection Patients in The Inpatient Room of Granmed Hospital Lubuk Pakam - Purba, Novandi; Br. Turnip, Nur Ulina M; Situmorang, Novidawati; Alfrisa, Bagus; Karokaro, Tati Murni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Acute Respiratory Infection is one of the main causes of death in children in developing countries. ISPA is a disease of the upper or lower respiratory tract that usually infects and can cause various diseases ranging from asymptomatic or mild to severe inflammation. Lethality depends on environmental factors and predisposing factors. Acute Respiratory Infection is still often a major health problem because it is the main cause of death and disease in the world. Upper respiratory tract infection is a cause of death and morbidity in infants and children in Indonesia. The types of antibiotics that are often consumed to treat acute respiratory infections are penicillins and cephalosporins, such as amoxicillin, ceftriaxone, and cefotaxime. The method used for this dedication is the open and community training method or the online lecture method. The purpose of this community service is to provide information about the use of antibiotics to ARI patients at Grandmed Hospital. The activity was carried out in the form of online discussions via zoom with several patients and people who suffer from ISPA. The results obtained in this study were more male patients with ISPA than women. This condition is associated with high physical activity in boys and can quickly worsen physical conditions, including the immune system. In this study, patients were given a questionnaire to ensure that the information conveyed by the presenting team was properly conveyed and understood. In this activity, patients must understand the evaluation of the use of antibiotics in ARI so that in the future patients who suffer from it will get clear information.